The healthy workplace : how to improve the well-being of your employees--and boost your company's bottom line - Stringer, Leigh (Business professional collection, 2016)
The Healthy Workplace proves that it pays to invest in your people's well-being and reveals how to: Create a healthier, more energizing environment Reduce stress to enhance concentration Inspire movement at work Use choice architecture to encourage beneficial behaviors Support better sleep Heighten productivity without adding hours to the workday. Filled with tips for immediate improvement and guidelines for building a long-term plan, The Healthy Workplace will boost both employee well-being and the bottom line.